Good morning, gorillas - Osborne, Mary Pope.; Murdocca, Sal (New York : Random House, 2002)
The magic tree house takes Jack and Annie to an African rainforest, where the siblings encounter gorillas and learn to communicate with them.
"A Stepping Stone book.".
Horn Book.
3.7
3-6
Keywords: Annie (Fictitious character) -- Fiction; Gorilla -- Fiction; Human-animal communication -- Fiction; Jack (Fictitious character : Osborne) -- Fiction; Magic -- Fiction; Time travel -- Fiction; Tree houses -- Fiction; Animal communication -- Fiction; Annie (Fictional character : Osborne) -- Fiction; Gorillas -- Fiction; Jack (Fictional character : Osborne) -- Fiction; Magic -- Fiction; Time travel -- Fiction; Tree houses -- Fiction; Africa -- Fiction; Africa -- Fiction